Cordycepin Nanoencapsulated in Poly(Lactic-Co-Glycolic Acid) Exhibits Better Cytotoxicity and Lower Hemotoxicity Than Free Drug - Marslin G (Dove Medical Press, 2020)
Gregory Marslin,1– 3 Vinoth Khandelwal,4 Gregory Franklin5 1School of Pharmacy, Sathyabama Institute of Science and Technology, Jeppiaar Nagar, Rajiv Gandhi Salai, Chennai 600119, India; 2Ratnam Institute of Pharmacy and Research, Nellore, 524346, India; 3College of Biological Science and Engineering, Shaanxi University of Technology, Hanzhong, Shaanxi, People’s Republic of China; 4Department of Translational Pharmacology, Santa Maria Imbaro, Italy; 5Institute of Plant Genetics of the Polish Academy of Sciencs, Strzeszyńska 34, Poznań 60-479, Wielkopolska, PolandCorrespondence: Gregory Marslin; Gregory Franklin Tel +91 4424502344Email marslingregory@gmail.com; fgre@igr.poznan.plPurpose: Cordycepin, a natural product isolated from the fungus Cordyceps militaris, is a potential candidate for breast cancer therapy. However, due to its structural similarity with adenosine, cordycepin is rapidly metabolized into an inactive form in the body, hindering its development as a therapeutic agent. In the present study, we have prepared cordycepin as nanoparticles in poly(lactic-co-glycolic acid) (PLGA) and compared their cellular uptake, cytotoxicity and hemolytic potential with free cordycepin.Materials and Methods: Cordycepin-loaded PLGA nanoparticles (CPNPs) were prepared by the double-emulsion solvent evaporation method. Physico-chemical characterization of the nanoparticles was done by zetasizer, transmission electron microscopy (TEM) and reverse-phase high-pressure liquid chromatography (RP-HPLC) analyses. Cellular uptake and cytotoxicity of CPNPs and free drug were tested in human breast cancer cells (MCF7). Hemolytic potential of both of these forms was evaluated in rat red blood cells (RBCs).Results: Physico-chemical characterization revealed that CPNPs were spherical in shape, possessed a size range of 179– 246 nm, and released the encapsulated drug sustainably over a period of 10 days. CPNPs exhibited a high level of cellular uptake and cytotoxicity than the free drug in MCF-7 cells. While CPNPs were not toxic to rat RBCs even at high concentrations, free cordycepin induced hemolysis of these cells at relatively low concentration.Conclusion: Our results reveal that delivery as CPNPs could enhance the clinical efficacy of cordycepin substantially.Keywords: cordycepin, nanoparticles, PLGA, cellular uptake, cytotoxicity, breast cancer cells, hemolysis